(untitled) (Journal of Engineering, 2023)
An experimental study is made here to investigate the discharge coefficient for contracted rectangular Sharp crested weirs. Three Models are used, each with different weir width to flume width ratios (0.333, 0.5, and 0.666). The experimental work is conducted in a standard flume with high-precision head and flow measuring devices. Results are used to find a dimensionless equation for the discharge coefficient variation with geometrical, flow, and fluid properties. These are the ratio of the total head to the weir height, the ratio of the contracted weir width to the flume width, the ratio of the total head to the contracted width, and Reynolds and Weber numbers. Results show that the relationship between the discharge coefficient and these variables is a non-linear power function with a determination coefficient of 0.97. The importance and normalized importance analysis show that 56.3 % of the discharge coefficient variation is explained by the head-to-contracted width of the weir ratio followed by lower effects of the other variables, namely 16.5, 13.7, 12.4, and 1.2 % for contracted width to flume width ratio, Reynolds number, the head to the contracted width ratio, and Weber, respectively. The effect of the Weber number on the discharge coefficient is much lower than that of the Reynolds number.